The influence of the alloying of the auger by the chromium on its wear during dehydration process of municipal solid waste in the garbage truck - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O. (Problems of Tribology, 2022)
The article is dedicated to the study of the influence of the alloying of the auger by the chromium on its wear during dehydration of solid waste in the garbage truck. Using the method of regression analysis, the hyperbolical dependencies of auger wear depending on the chromium content in its hardened steel for different values of the friction path are determined. Graphical dependences of augur wear depending on the chromium content in its hardened material as a function ​​of the friction path are made up, and it confirms sufficient convergence of the obtained dependencies. Carried out additional regression analysis allowed to determine that that during two weeks of operation of the auger during dehydration of solid waste in the garbage truck increasing of the chromium content in its hardened material from 0.25% to 12% reducing the speed of the wearing and energy consumption of solid waste dehydration from 12.2% to 3.1%, and, consequently, to reduce the cost of the process of their dehydration in the garbage truck. It is shown the graphical dependence of the reduction of energy consumption of dehydration of solid household waste by the hardened auger due to its alloying by the chromium. It was established the expediency of further research to determine the rational content and structural state of the material of the auger and the ways to increase its wear resistance.